Adobe Type Library Reference Book (Adobe Press : Peachpit Press, 2008)
Choosing the right font can be one of the hardest parts of your job as a digital designer-there are literally thousands to choose from. One of the largest and most respected collections of high-quality fonts is the Adobe Type Library, now available entirely in the cross-platform OpenType® format, which promises to make font incompatibilities a thing of the past. Any designer who has struggled to find just the right typeface for a project will find this comprehensive reference an indispensable guide to Adobe's vast selection of over 2,200 typefaces. Organized both alphabetically and by style, the newly revised and updated Adobe Type Library Reference Book, Third Edition provides: Specimen pages displaying every font in Adobe's enormous collection, including 60 new typefaces Typefaces from internationally renowned foundries and award-winning type designers Design inspiration and expert advice on type selection An expanded section on the OpenType format to help you make the most of its expanded character set and layout capabilities Explanations and illustrations of the distinguishing characteristics of different type styles-from a graceful Garalde Oldstyle to Adobe's new Opticals-as well as ornaments and symbols A chart showing the Adobe Western 2 character set, including the right keyboard combinations to access different characters Listings for 31 Japanese fonts from Adobe.